(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to demonstrate the role of sustainable budget requirements in improving the Iraqi financial situation through the use of a set of requirements to be relied upon when preparing the budget, and to achieve the objectives of the research, a study was conducted of the indicators of the Iraqi economy for the years (2004-2021). A set of conclusions and recommendations were reached, the most prominent of which is that Iraq relies heavily on non-renewable financial resources, and this exposes its economy more to financial crises as a result of fluctuating prices of non-renewable resources. Accordingly, it is necessary to find renewable financial resources that can be relied upon in the event of a recession occurring for non-renewable resources. As a large proportion of Iraq’s resources go to pay off debts because of its heavy dependence on these resources, the prices of which fluctuate from one period to another, as happened in the years (2008, 2016, 2020). Therefore, attention must be paid to the requirements of the sustainable budget because of their significant role in reviving the Iraqi financial situation. The research also recommends Iraq’s interest in renewable financial resources because it represents an important alternative that can be resorted to in the event of fluctuating oil prices instead of relying on debt.